Effect of silver nanoparticles on the DC conductivity in chitosan-silver triflate polymer electrolyte - Aziz, Shujahadeen B.; Abidin, Zul Hazrin Zainal; Arof, Abdul Kariem (Elsevier, 2010)
A solid polymer electrolyte composed of chitosan and silver triflate (AgCF(3)SO(3)) has been prepared by the solution cast technique. The formation of polymer-salt complex has been confirmed by X-ray diffraction. The DC electrical conductivity of chitosan-silver triflate electrolyte has been investigated between 303 and 423 K, using electrochemical impedance spectroscopy over the frequency range from 50 Hz to 1000 kHz. The conductivity was found to increase with increase in AgCF(3)SO(3) concentration at room temperature. The DC conductivity obeys Arrhenius relationship up to a particular temperature and decreases at higher temperatures due to decrease in silver ions as a result of the formation of silver nanoparticles. The presence of an additional semicircular arc in the Cole-Cole plot obtained above 328 K indicates the existence of grain boundaries, which can be attributed to the silver particles. The presence of silver particles also have been proven by XRD after heating at 333, 363, and 393 K where the (1 1 1) peak of Ag is observed to increase with temperature. The silver particles were shown to be of nanosize using transmission electron microscopy (TEM). (C) 2010 Elsevier B.V. All rights reserved.